Pengaruh Ukuran Perusahaan, Opini Audit dan Kepemilikan Publik Terhadap Audit Delay - Feline Chiquita; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine and analyze the effect of firm size, audit opinion and stock ownership on audit delay. The population in this study is all companies in the property and real estate sector listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique uses the purposive sampling method which produces a sample of 39 companies with a total of 195 observations. The data analysis method used is multiple regression analysis with a fixed effect model approach. The results of the partial test show that firm size has a positive effect on audit delay, audit opinion has no effect on audit delay and public ownership has a negative effect on audit delay.